Respuesta :
Answer:
No solution
Step-by-step explanation:
Simplify the left side.
− 3 x − 10 =3 ( 3 − x )
Simplify
3 ( 3 − x ).
− 3 x − 10 = 9 − 3 x
Move all terms containing x to the left side of the equation.
− 10 = 9
Since
− 10 ≠ 9 , there are no solutions.
No solution
No solution
Step-by-step explanation:
Simplify the left side.
− 3 x − 10 =3 ( 3 − x )
Simplify
3 ( 3 − x ).
− 3 x − 10 = 9 − 3 x
Move all terms containing x to the left side of the equation.
− 10 = 9
Since
− 10 ≠ 9 , there are no solutions.
No solution
Read more on Brainly.com - https://brainly.com/question/14144021#readmore
Step-by-step explanation:
Simplify the left side.
− 3 x − 10 =3 ( 3 − x )
Simplify
3 ( 3 − x ).
− 3 x − 10 = 9 − 3 x
Move all terms containing x to the left side of the equation.
− 10 = 9
Since
− 10 ≠ 9 , there are no solutions.
No solution
Read more on Brainly.com - https://brainly.com/question/14144021#readmore